Analysis of Capital Punishment as a Last Resort in the National Criminal Justice System - Safaruddin Harefa (Presscience, 2027)
This study examines the evolving position of capital punishment within Indonesia’s criminal justice system in light of recent statutory reforms and persistent institutional shortcomings. Although Indonesia continues to retain and implement the death penalty, particularly for narcotics offenses, the enactment of KUHP 2023 and the emergence of the Draft Law on the Implementation of Death Penalty introduce a new conditional framework that formally positions execution as a last resort. Using a normative juridical method that analyzes legislation, judicial decisions, doctrinal writings, and international human rights instruments, this study evaluates the coherence of these reforms and their interaction with constitutional guarantees, fair-trial principles, and global penal trends. The findings reveal significant gaps between normative aspirations and institutional realities: inconsistencies in judicial reasoning, weaknesses in investigative procedures, ambiguous clemency standards, and limited correctional capacity undermine the reliability of capital sentencing. At the same time, the probationary model and conversion mechanism signal an emerging shift toward conditional retention that narrows—but does not eliminate—the scope of death penalty application. The study concludes that Indonesia’s current framework represents a transitional phase marked by partial alignment with human rights norms yet constrained by structural fragilities that hinder the realization of capital punishment as a genuine last-resort measure.